Diasporic youth identities of uncertainty and hope: second-generation Albanian experiences of transnational mobility in an era of economic crisis in Greece. (8th August 2016) - Michail, Domna; Christou, Anastasia
ABSTRACT: This paper explores various dimensions of 'gender' and 'mobility' among immigrant youth from a transnational perspective in an era of economic crisis. The extent and parameters of continuity, contestation and change in migrant youth identities are analysed and we suggest that neither gender nor identity are stable categories but are embedded in sociocultural particularities both in the country of residence (Greece) but also in the country of origin (Albania). Through in-depth interviews with 52 participants, all second-generation Albanian immigrants in Greece born to two Albanian parents, the paper addresses youth identification in relation to gendered representations of belonging. The narrative accounts that we have selected and analysed reflect the emotional challenges, constraints and creativity of Albanian youth.